Morbidity and Mortality Factors Analysis of Caesarean Section - Ratna Dewi Puspita Sari; Winda Trijayanthi Utama; Ratu Nirmala Wahyunindita (GLOBAL HEALTH SCIENCE GROUP, 2021)
Caesarean Section is the most common obstetric surgery performed today. CS delivery without medical indication increases the risk of maternal morbidity and mortality 3-5 times higher than vaginal delivery techniques. The increased risk of morbidity and mortality in CS delivery is due to complications caused, during intraoperative or postoperative. Lampung Province is one of the provinces with the highest MMR value in Indonesia (148 per 100,000 live births) with a CS birth selection of 13.18%. The aim of this research is to analyze the characteristics of factors associated with maternal morbidity and mortality in CS delivery. Both morbidity groups characteristics (case and control) show correlations were found between maternal age (p<0.02), obstetric complication (p<0.01), education (p<0.02) and the incidence of maternal deaths. Meanwhile, parity and delivery complication variables did not show significant. correlations to maternal deaths (p>0.05). Both mortality groups characteristics (case and control) show correlations were found between maternal age (p<0.02), obstetric complication (p<0.05), education (p<0.03), delivery complication (p<0.04) and the incidence of maternal deaths. Meanwhile, maternal age and parity variables did not show significant. corelations to maternal deaths (p>0.05).